2017
DOI: 10.1021/acs.jafc.6b04695
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant Activity during the Development of ‘Brookfield’ and ‘Mishima’ Apples

Abstract: The aim of this study was to characterize the changes in the contents of total (TPC) and individual (IPC) phenolic compounds, the total antioxidant activity (TAA) in the peel and pulp, and total anthocyanins (TAN) in the peel during the development of the fruits of 'Brookfield' and 'Mishima' apple trees. 'Brookfield' apples were harvested from the 49th to the 138th days after full bloom (DAFB) and 'Mishima' apples from the 45th to the 172th DAFB. In the pulp, the IPC, TPC, and TAA rapidly reduced at 75 and 79 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
6
11
0
Order By: Relevance
“…These data confirm previous studies where catechin, epicatechin and chlorogenic acid are the major contributors to the antioxidant capacity of apples [4,39]. The significant correlation between phloretin and antioxidant capacity has never been reported, it can be explained on the particularly high average content in phloretin of the apple varieties studied, and need further investigation.…”
Section: Dpph Scavenging Activity and Total Phenolic Contentsupporting
confidence: 91%
“…These data confirm previous studies where catechin, epicatechin and chlorogenic acid are the major contributors to the antioxidant capacity of apples [4,39]. The significant correlation between phloretin and antioxidant capacity has never been reported, it can be explained on the particularly high average content in phloretin of the apple varieties studied, and need further investigation.…”
Section: Dpph Scavenging Activity and Total Phenolic Contentsupporting
confidence: 91%
“…The consumption of apples is a major source of phenolic compounds, and the skin portion provides the highest concentrations (WOLFE et al, 2003;STANGER et al, 2017;.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the accumulation patterns of bioactive phenolic, the changes of antioxidant activities and further select the best harvest time for cereals and fruits with higher nutrition values, the maturation processes have gain a lot of attractions from many researchers (Stanger et al, 2017). Researchers investigated the changes of nutrition in apricots and found that the total phenolic content and the total antioxidant activity of apricot had increased about 8fold and 3.5-fold during maturation, respectively (Campbell et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the changes of phenolic contents and antioxidant activities have been widely studied in many plants and fruits (Techakanon et al, 2016;Stanger et al, 2017). However, less reports of phenolics biosynthesis and the changes of antioxidant activities in sweet corn varieties during kernel maturation have not been investigated.…”
Section: Introductionmentioning
confidence: 99%